The Implementation of Human Resource Management Policies in Increasing Student Participation and Engagement in Academic Activities - Sami'un, Sami'un; Salim, Agus; Ningrum, Sari Kartika (OMNICODE Journal (Omnicompetence Community Developement Journal), 2024)
This research aims to analyze the implementation of Human Resource Management (HRM) policies in increasing student participation and engagement in academic activities at the Faculty of Cultural Management and Business. The study utilized a qualitative approach, including interviews, surveys, and document analysis to gather data. Results indicated that effective HRM policies positively impacted student involvement, particularly through training programs, resource provision, and a supportive learning environment. Key challenges included the gap between theory and practice, along with limited access to advanced training due to time constraints. The findings emphasize the need for continuous evaluation and integration of flexible training opportunities to improve student engagement and academic achievement.